Programa Etnomatemática: ponderações da prática pedagógica - Justi, Jeane Cristina (2015)
The aim of this present work is investigating the interest and motivation for learning, awakened in pupils when the educator practice is guided by the ethnomathematics perspective. The main question is: Can an ethnomathematic approach awaken enthusiasm in pupils, causing it to become more critic and active in building their knowledge? The methodology that guides the investigation is qualitative, based on technical arising of the ethnographic case study. Theoretical contributions that support the investigation are from the scientific methodology and from ethnomathematics. The research material is composed by: researcher’s field diary, audio recording of participant observation, interviews reports of community residents and students parents, highlighting the material produced by students. This study was developed on an 8º year of high school of rural community. During the work were prioritized the ethnomathematics concepts of the Ethnomathematic Program, which establish a link exchange, where the lecturers inserts themselves on the reality of pupils in a way that promote an appreciation of their identity and a commitment to their learning. The educator investigates and values the ideas of pupils throughout dialogues. There are challenges for the application of education with ethno mathematic perspective, pointed out by authors, listed and supplemented in the research. In this context, it is believed that the socio-cultural knowledge must be respect, and as they are understood their specialties, capabilities and characteristics, this can guide teaching practice, making significant process for pupils, providing appropriation of scientific knowledge. Analysis of research practice indicated that students, research subjects, when they decided contextual issues, with their way of life, felt appreciated. The conclusion is that, with continuous action of contextualized of school mathematics, from the recognition of the environment and of cultural identity, the educator has the opportunity of review their own participant condition, and therefore promote an enthusiasm for learning. Because a motivated pupil becomes active, since that the all project is guided in a significant theme.